Performance Analysis of Recycled Low Density Polyethylene Laminated Waste Denim Fabrics to be Used in Recycled Shopping Bags - Sezgin, Hande; Gelmez, Koray; Yalcin-Enis, Ipek (Zenodo, 2021)
Introduction: Solid waste, which increases day by day, is a harbinger of an increasing environmental risk factor worldwide (1). Among solid wastes, plastic and textile wastes have significant amount. Polyethylene accounts for 50% of the total packaging waste and 11% of total solid waste by weight (2). On the other hand, although textile is a necessity in human life, excessive production and consumption as well as shortage of raw materials cause environmental risks to come to the fore (3). Methods: Waste bottle caps (low density polyethylene, LDPE) and the waste denim fabrics (content: 98% cotton / 2% elastane, basis weight: 331 g/m2, provided by Çalık Denim) are used to produce laminated fabrics. 20 tons of pressure and 140°C heat are applied for 1 hour to form LDPE matrix plates in hot press machine. A fabric layer and a LDPE plate are placed one over another and subjected to heat and pressure, again. F (denim fabric), L (LDPE plate) and LF (Laminated structure) are subjected to performance analysis. The hydrostatic head tester is used for water resistance analysis in order to determine the water permeability of the samples (TS EN ISO 811). For the water resistance analysis of stitched samples, 3.5 stitches per 1 cm is applied. Drop-weight impact test is carried out with an energy of 12 J. Tensile strength test is applied to samples by using Titan2 universal testing machine according to TS EN ISO 13934-1. Results & Discussions: The fabric can resist to water only 0.59 h while L as well as L-F sample withstand heavy rain, wet snow and high pressure. On the other hand, L-F stitched samples can withstand water maximum 10.2 h which indicates the water diffuses from the needle gaps under pressure. In order to improve this structure, these stitched samples are pressed again under pre-mentioned pressure and temperatures to fill the holes created by the needles. After this process, the tested L-F stitched samples become also water resistant. The drop-weight impact test results show that the absorbed energy and the maximum displacement increase for L-F samples while the maximum load value is similar to sample F. Thus, it can be said that the composite effect can be observed from L-F samples. The maximum tensile force applied to fabric warp specimen is higher than the maximum force applied to fabric weft specimen. The weft fabric samples show tear, whereas warp fabric samples do not show tear under force. It is observed from the results that the tensile strength value difference between warp and weft direction of the fabric is eliminated by the addition of matrix plate. Therefore, an isotropic structure is observed for L-F. Conclusions: By laminating the denim fabric with recycled LDPE plates, the water-resistant laminated fabrics with improved drop-weight impact resistance are produced. Although there is a slight decrement in tensile strength values of the denim fabrics based on the undesired sliding effect, the laminated structure still meets the tensile strength requirements of the shopping bags. Therefore, it is concluded that the laminated fabrics that are produced from waste components can be a promising material for shopping bags. Keywords: Recycling, Textile waste, Plastic waste, Performance analysis Acknowledgment: This study is funded by Istanbul Technical University, Scientific Research Projects (BAP, 42118). References 1. Tinmaz E, Demir I. Research on solid waste management system: to improve existing situation in Çorlu town of Turkey. Waste Manage. 2006;26: 307–314. 2. Ozturk O (2005). Determining the reusability of recycled polyethylene and polypropylene by tensile tests, Master Thesis, Pamukkale University, Turkey. 3. Yalcin-Enis I, Kucukali-Ozturk M, Sezgin H. Risks and management of textile waste. Nanoscience and Biotechnology for Environmental Applications, 2019
29-53, Springer.